دور استخدام نظريَّة صفوف الانتظار في تحسين جودة الخِدمة المَصرِفيَّة "دراسة حالة: المصرف التِّجاري السُّوري" - اسبر سعيد (Latakia University Journal - Economic and Legal Sciences Series, 2018)
لقد نالت جودة الخِدمة المَصرِفيَّة اهتماماً بالغاً من قبل الإداريِّين والأكاديميِّين والمُسوِّقين المَصرفيين، وذلك لما لها من قيمة استراتيجيَّة كبيرة ودوراً مُهمَّاً في تمكين المصرف من: الاحتفاظ بعملائه وموظَّفيه وجعلهم راضين، زيادة فُرص تقديم الخِدمات المصرفيَّة، جذب عُملاء جُدد، تطوير العلاقات بين العَميل والمصرف، تعزيز السُّمعة وتحسين الأداء المصرفي وفقاً لتوقُّعات العَميل، وبالتَّالي تحسين مستوى الربحيَّة. من هُنا جاء هذا البحث للوقوف على أهمِّيَّة الدَّور الذي يُمكن أن يلعبه استخدام نظريَّة صفوف الانتظار في تحسين جودة الخِدمة المصرفيَّة بأبعادها الخمسة (الملموسيَّة، الاعتماديَّة، الاستجابة، الأمان والتَّعاطُف) في المصرف التِّجاري السُّوري، وذلك من وجهة نظر العاملين فيه. قام الباحث بتوزيع (150) استبياناً على عيِّنة من العاملين في فروع المصرف التِّجاري السُّوري العاملة في دمشق، الَّلاذقيَّة، طرطوس وحمص، وبلغ عدد الاستبانات المستردَّة والصَّالحة للتَّحليل والَّتي تمَّ تفريغها (100) استبانة. قام الباحث بتحليل البيانات باستخدام برنامج التَّحليل الإحصائي (SPSS 20). وفي نهاية هذا البحث توصَّل الباحث إلى مجموعة من الاستنتاجات وأهمّها: يوجد تأثير معنوي لاستخدام نظريَّة صفوف الانتظار في تحسين جودة الخِدمة المصرفيَّة بأبعادها الخمسة (الملموسيَّة، الاعتماديَّة، الاستجابة، الأمان والتَّعاطُف) في المصرف التِّجاري السُّوري. كما تقدَّم الباحث في نهاية البحث بمجموعة من التَّوصيات والَّتي كان أهمُّها: ضرورة تطبيق نظريَّة صفوف الانتظار في جميع فروع المصرف التِّجاري السُّوري، والعمل على التَّحسين المستمر لنمط التَّقانة المُستخدم والمرافق والتَّجهيزات والأدوات والمعدَّات المَصرِفيَّة والإداريَّة الخاصَّة بالمصرف، ورفع مستوى الالتزام بالوعود المقدَّمة للعُملاء والمراجعين، وتحفيز العاملين على مساعدتهم والاهتمام بحلِّ مشاكلهم والرَّد على استفساراتهم. The quality of the banking service has received great attention from administrators, academics and bank marketers because of its great strategic value and an important role in enabling the bank to: Keep its customers and employees satisfied, increase the opportunities to provide banking services, attract new customers, Enhance reputation and improve banking performance according to client expectations, thus improving profitability level. This research describes the importance of the role that the use of queue theory can play in improving the quality of banking services in its five dimensions (tangibles, reliability, responsiveness, assurance and empathy) in the Commercial Bank of Syria, from the point of view of its employees. The researcher distributed (150) questionnaires on a sample of workers in the branches of the Commercial Bank of Syria operating in Damascus, Lattakia, Tartous and Homs. The number of questionnaires retrieved and valid for the analysis was discharged (100). The researcher analyzed the data using the Statistical Analysis Program (SPSS 20). At the end of this research, the researcher reached a number of conclusions, the most important of which is: There is a significant effect on the use of queue theory in improving the quality of banking service in its five dimensions (tangibles, reliability, responsiveness, assurance and empathy) in the Commercial Bank of Syria. The researcher also presented a set of recommendations at the end of the research, the most important of which is: the necessity of applying the theory of waiting lines in all branches of the Commercial Bank of Syria, and work on continuous improvement of the type of technology used, facilities, equipment, tools and banking and administrative equipment of the bank. The workers help them and pay attention to solving their problems and answering their queries.